A lake house holiday eaudiobook - Squires, Megan (Tantor Media, 2020)
Sometimes you need to get away to find the place your heart calls home. Jolene Carter lives in Merrylark Lake, a quaint town where neighbors are like family and vacationers become fast friends. With her dream of opening a downtown storefront on hold, Jolene volunteers wherever she can, whether it be at Cat's Coffee Cart or the town's annual tree lighting. It is while she's tending to her neighbor's vacation rental that Jolene meets Luke, a cowboy with a mustang rescue and a past he's hoping to leave back at the ranch. Luke Handley isn't one to believe in holiday magic. That disappeared when his winter wedding was called off and his honeymoon was canceled. But the more time he spends in Merrylark, the more he's convinced this magic exists. When Luke's ex unexpectedly shows up as the other half to the lake house reservation, things get complicated. Luke knows all the magic in the world won't clear up this misunderstanding. If he's learned anything from Jolene, though, it's that helping others is the most effective way to show love. With a surprise up his sleeve and a little help from his new Merrylark friends, Luke hopes he's able to do just that.